Intra‐Abdominal Cooling System Limits Ischemia–Reperfusion Injury During Robot‐Assisted Renal Transplantation. Issue 1 (24th July 2017) - Meier, R. P. H.; Piller, V.; Hagen, M. E.; Joliat, C.; Buchs, J.‐B.; Nastasi, A.; Ruttimann, R.; Buchs, N. C.; Moll, S.; Vallée, J.‐P.; Lazeyras, F.; Morel, P.; et al.
Abstract : Robot‐assisted kidney transplantation is feasible; however, concerns have been raised about possible increases in warm ischemia times. We describe a novel intra‐abdominal cooling system to continuously cool the kidney during the procedure. Porcine kidneys were procured by standard open technique. Groups were as follows: Robotic renal transplantation with (n = 11) and without (n = 6) continuous intra‐abdominal cooling and conventional open technique with intermittent 4°C saline cooling (n = 6). Renal cortex temperature, magnetic resonance imaging, and histology were analyzed. Robotic renal transplantation required a longer anastomosis time, either with or without the cooling system, compared to the open approach (70.4 ± 17.7 min and 74.0 ± 21.5 min vs. 48.7 ± 11.2 min, p‐values < 0.05). The temperature was lower in the robotic group with cooling system compared to the open approach group (6.5 ± 3.1°C vs. 22.5 ± 6.5°C; p = 0.001) or compared to the robotic group without the cooling system (28.7 ± 3.3°C; p < 0.001). Magnetic resonance imaging parenchymal heterogeneities and histologic ischemia–reperfusion lesions were more severe in the robotic group without cooling than in the cooled (open and robotic) groups. Robot‐assisted kidney transplantation prolongs the warm ischemia time of the donor kidney. We developed a novel intra‐abdominal cooling system that suppresses the noncontrolled rewarming of donor kidneys during the transplant procedure and prevents ischemia–reperfusion injuries. Abstract : The authors use a novel intra‐abdominal cooling system to continuously cool the donor kidney during robot‐assisted kidney transplantation in a pig model and show that this strategy prevents noncontrolled rewarming during the anastomosis and reduces ischemia–reperfusion injury.